Structural, optical and conductivity investigations on kappa-Al2O3 ceramics for powder metallurgical production and sensitivity applications - YUMAK YAHŞİ, AYŞE (ELSEVIER SCI LTD, 2016)
Aluminum oxide (Al2O3) ceramics has been prepared by spray pyrolysis technique. X-ray analysis shows that the prepared thin films crystallize in kappa-Al2O3 (kappa-alumina) phase with orthorhombic structure. Also, the crystallites are mainly orientated along (201) direction. The dispersion of the refractive index was discussed in terms of single oscillator model proposed by Wemple and Di-Domenico. The single oscillator energy (E-0) as well as the dispersion energy (E-d) was therefore calculated. Finally electrical properties were performed using impedance spectroscopy technique in the frequency range 5 Hz to 13 MHz at various temperatures (300-400 degrees C). DC conductivity was thermally activated, showing a semiconductor behavior of kappa-Al2O3 sprayed thin films. Elements from the Lattice Compatibility Theory analyses have been also presented in order to give a plausible understanding for the recorded chlorine/oxygen rapid substitution within AlCl3 lattices. On the other hand AC conductivity was investigated through Jonscher law. The imaginary part of the complex impedance has a maximum whose relaxation frequency increases with temperature according to the Arrhenius law. Values of dielectric constants were calculated. (C) 2015 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Optical properties; kappa-Al2O3 ceramics; Surface coating; Impedance spectroscopy; Lattice Compatibility Theory (LCT); COMPATIBILITY THEORY LCT; SPRAYED THIN-FILM; LATTICE COMPATIBILITY; PHYSICAL INVESTIGATIONS; SUBSTRATE-TEMPERATURE; OPTOTHERMAL EXPANSIVITY; AC CONDUCTIVITY; OXIDE; ZNO; ALPHA-AL2O3